Serpentinization in the Archean and Early Phanerozoic – Insights from chromium isotope and REY systematics of the MgCr hydroxycarbonate stichtite and associated host serpentinites - Kraemer, Dennis; Frei, Robert; Ernst, David M.; Bau, Michael; Melchiorre, Erik (Chemical geology, 2021)
Chromium isotopes have emerged as powerful redox proxies for past ocean-atmosphere systems as shifts in Cr isotope ratios towards heavier isotope compositions are indicative of Cr redox cycling on Earth. Knowledge of the Cr cycle in the critical zone and the fate of Cr during serpentinization and other hydrothermal processes is therefore important to assess the geologic interpretation of Cr isotopes in the rock record. An investigation of the trace element geochemistry of stichtite may provide such insights by shedding new light on the conditions of past serpentinizing environments. Stichtite, a magnesium‑chromium-bearing hydroxycarbonate, is a rare mineral that forms during serpentinization by conversion of chromite and other Cr-rich spinels. Its occurrence is restricted to Archean and Early Phanerozoic serpentinite bodies on ancient cratons and to mine waste. In this contribution, Cr isotope and rare earth elements and Y (REY) systematics in stichtites and their respective serpentinite hosts were investigated. This comparative study of Archean and Early Phanerozoic stichtites from different localities in South Africa, Western Australia, and Tasmania revealed variable Cr isotope fractionation with δ53Cr ranging from −0.145 ± 0.052‰ up to +0.24 ± 0.04‰ in the stichtites. The serpentinites are less fractionated with δ53Cr ranging from −0.13 ± 0.04‰ to +0.05 ± 0.02‰ and show a fractionation similar to the terrestrial mantle δ53Cr inventory. Whereas δ53Cr of all stichtites, except of one, are within the chromite array, the deviations from host serpentinites indicate that Cr was subject to Cr cycling during serpentinization. The variable Cr isotope ratios of stichtite reflect a complex interplay of several physicochemical processes. These are difficult to identify solely from isotope compositions as the resulting Cr isotope fractionation represents the net result of all processes that affect the complex Cr cycling in the critical zone. The very first REY concentration data for stichtite further corroborate the notion that stichtite formation is indeed not an isochemical process and that its formation involves intense metal mobility during associated metasomatism. Rare earth elements and yttrium are depleted in the stichtites relative to the serpentinites, but the overall similar REYCN patterns indicate that the REY in both, the serpentinites and stichtites, were sourced from a chemically similar fluid that was dominated by interaction with the serpentinized rocks. Seawater and marine carbonates can be excluded as potential contributors towards REY inventory of stichtite. The presence of superchondritic Y/Ho ratios in stichtite further emphasizes intense water-rock interaction at high CO32− and HCO3− activities. Positive EuCN anomalies in some stichtites and serpentinites point to reducing conditions with regard to the Eu3+/Eu2+ redox couple and temperatures in excess of 250 °C at the site of REY mobilization, prior to stichtite formation. Lack of Ce anomalies in stichtite further confirm reducing conditions at the site of stichtite formation.